Human Case of Ehrlichia chaffeensis Infection, Taiwan - Peng, Shih-Huan; Yang, Su-Lin; Ho, Yu-Ni; Chen, Hsiang-Fei; Shu, Pei-Yun (Emerging infectious diseases, 2019)
In 2018, an immunosuppressed woman in southern Taiwan had onset of fever, chills, myalgia, malaise, thrombocytopenia, lymphocytopenia, and elevated hepatic transaminases. Investigation revealed infection with Ehrlichia chaffeensis. This autochthonous case of human monocytotropic ehrlichiosis was confirmed by PCR, DNA sequencing, and seroconversion.